EFFECT OF SCALE - Karimov Bekzod Qayumovich; Suleymanova Mohitabona Elbek qizi; Abdug‘aniyeva Zulxumor Alijon qizi (Journals Park Publishing, 2024)
This article provides a comprehensive explanation of the role of economies of scale in production, including the theories of economists from past centuries. it is used to get more profit. It can be seen that this topic is very important for every entrepreneur and business people.
Keywords: Scale effect, long-term and short-term costs, intensive growth, extensive growth, large businesses, small businesses, break-even point, law of diminishing returns.